REVOLUSI AKUNTANSI MODERN DENGAN ARTIFICIAL INTELLIGENCE - Agustin Ekadjaja; Maria Bernadet Pek; Florence Delvina (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Tarumanagara, 2025)
This Community Service Activity (PKM) is one of the implementations of the Tri Dharma of Higher Education, especially in making a real contribution to society. This program is intended for high school students and students. The implementation of the activity was carried out through face-to-face direct training. The activity began with an initial meeting this was to identify the needs of the school in order to establish cooperation. The theme raised in this activity was